2013
DOI: 10.1371/journal.pone.0072767
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Notch Pathway Expression during Mouse Testis Post-Natal Development and along the Spermatogenic Cycle

Abstract: The transcription and expression patterns of Notch pathway components (Notch 1–3, Delta1 and 4, Jagged1) and effectors (Hes1, Hes2, Hes5 and Nrarp) were evaluated (through RT-PCR and IHC) in the mouse testis at key moments of post-natal development, and along the adult spermatogenic cycle. Notch pathway components and effectors are transcribed in the testis and expressed in germ, Sertoli and Leydig cells, and each Notch component shows a specific cell-type and time-window expression pattern. This expression at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 55 publications
(94 reference statements)
6
54
0
Order By: Relevance
“…The role of Notch in the rodent testis remains controversial. Some reports suggest a possible role for Notch1 in the niche during spermatogenesis (Dirami et al, 2001;Hayashi et al, 2001;Murta et al, 2013), but functional studies could not demonstrate an essential function for Notch1 (Batista et al, 2012;Hasegawa et al, 2012). If N1IP::Cre HI is activated in germ cells during spermatogenesis, it will result in germline inheritance of an active reporter, manifest in uniform lacZ expression (stained blue by X-gal) in offspring of N1IP::Cre HI ; Rosa R26R/R26R fathers.…”
Section: Resultsmentioning
confidence: 99%
“…The role of Notch in the rodent testis remains controversial. Some reports suggest a possible role for Notch1 in the niche during spermatogenesis (Dirami et al, 2001;Hayashi et al, 2001;Murta et al, 2013), but functional studies could not demonstrate an essential function for Notch1 (Batista et al, 2012;Hasegawa et al, 2012). If N1IP::Cre HI is activated in germ cells during spermatogenesis, it will result in germline inheritance of an active reporter, manifest in uniform lacZ expression (stained blue by X-gal) in offspring of N1IP::Cre HI ; Rosa R26R/R26R fathers.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, we hypothesize that JAGGED1 of Sertoli cells activates Notch signaling in germ cells. The testicular localization of Notch receptors in mouse testes has been reported in several studies [Dirami et al, 2001;Mori et al, 2003;von Schonfeldt et al, 2004;Hasegawa et al, 2012;Murta et al, 2013], but these reports are not consistent for NOTCH1/2 localization. In contrast, these reports were in accordance with NOTCH3 localization in spermatogonia [Dirami et al, 2001;Mori et al, 2003;Murta et al, 2013].…”
Section: Introductionmentioning
confidence: 84%
“…2 ). Previous investigations had reported that spermatogonia expressed NOTCH3 in mouse testes [Dirami et al, 2001;Mori et al, 2003;Murta et al, 2013], but the differentiation state of NOTCH3-expressing spermatogonia had not yet been analyzed. Our work is the first to reveal the differentiation state of NOTCH3-expressing spermatogonia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in general, Mvh and Oct4 are taken as the markers of germ stem cells. The NOTCH1 surface receptor is a key molecule in the Notch pathway; their expression can prompt the activity of the Notch pathway [34,35]. Hairy and enhancer of split 1 (Hes1) and hairy and enhancer of split 5 (Hes5) are the principal target genes of the Notch pathway, which regulate the proliferation and differentiation of cells [36,37].…”
Section: Discussionmentioning
confidence: 99%